Effects of 1-Deoxynojirimycin on glycemic control: A systematic review and meta-analysis - In Ho Cho; RanRan Cheng; Cheol Woon Jung; Tae Hyung Won; Daijie Wang; Hwan-Hee Jang; In Guk Hwang; Sung Won Kwon (NFS Journal)
This meta-analysis investigates the effects of 1-Deoxynojirimycin (DNJ), derived from mulberry leaves, on glycemic control in individuals with impaired glucose tolerance and type 2 diabetes. DNJ significantly reduced postprandial plasma glucose (PPG) at 30 min, postprandial plasma insulin (PPI) at 30 min, and both glucose and insulin incremental area under the curve (iAUC) at 120 min, with substantial heterogeneity across studies. These findings align with DNJ's role as an inhibitor of α-glucosidase and sucrase, delaying carbohydrate digestion and glucose absorption in the small intestine. However, the effects were short-lived, indicating DNJ's limited prolonged efficacy due to low bioavailability and rapid clearance. Future research is needed to further investigate its long-term effects and improve its therapeutic potential.